Reviving The Turāṡ of Islamic Law: An Uṣūl al-Fiqh Review for Time Value of Money Concept: Revitalisasi Turāṡ Hukum Islam: Telaah Usul Fikih atas Konsep Nilai Waktu terhadap Uang - Muhammad, Afif; Burhani, Nasih; Humaidi, Humaidi (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2024)
Abstract: The concept of the time value of money (TVM) is a foundational element in conventional finance, yet its application within Islamic law remains a subject of conceptual and normative debate. This study aims to reassess the notion of TVM through the lens of turāṡ in Islamic legal theory (Uṣūl al-Fiqh), with particular focus on the perspectives of the four major Sunni schools (Ḥanafī, Mālikī, Syāfi‘ī, and Ḥanbalī). Employing a normative-legal approach and a library-based research method, this article explores how classical jurists differentiate between the permissibility of time-related value in credit-based sales contracts and its prohibition in loan-based transactions involving riba. The findings suggest that Islamic law recognizes time value only within a limited scope, embedded in the price of goods in deferred sales, but rejects the monetization of time as a stand-alone commodity in loan arrangements. Foundational legal juridical principles derived from Uṣūl al-Fiqh and the objectives of Islamic law (maqāṣid asy-sharī‘ah), such as justice, property preservation, and benevolence, provide the ethical and juridical basis for this distinction. The study concludes that TVM is Sharīʿah-compliant only when applied within the framework of real economic transactions, not in exploitative financial mechanisms. This research remains limited to conceptual legal analysis and does not assess practical applications in the Islamic finance industry. Future studies are encouraged to explore TVM implementation in contemporary Islamic financial products and its relevance to international standards and regulatory frameworks. Abstrak: Konsep nilai waktu uang (TVM) merupakan unsur dasar dalam keuangan konvensional, namun penerapan konsep ini dalam hukum Islam masih menjadi subjek perdebatan konseptual dan normatif. Penelitian ini bertujuan untuk mengevaluasi kembali konsep TVM melalui perspektif turāṡ dalam teori hukum Islam (Uṣūl al-Fiqh), dengan fokus khusus pada pandangan empat mazhab Sunni utama (Ḥanafī, Mālikī, Syāfi‘ī, dan Ḥanbalī). Dengan menggunakan pendekatan normatif-hukum dan metode penelitian berbasis perpustakaan, artikel ini mengeksplorasi bagaimana ulama klasik membedakan antara kelayakan nilai waktu dalam kontrak penjualan kredit dan larangan nilai waktu dalam transaksi pinjaman yang melibatkan riba. Temuan menunjukkan bahwa hukum Islam mengakui nilai waktu hanya dalam lingkup terbatas, tertanam dalam harga barang dalam penjualan tertunda, namun menolak monetisasi waktu sebagai komoditas mandiri dalam perjanjian pinjaman. Prinsip-prinsip hukum dasar yang berasal dari Uṣūl al-Fiqh dan tujuan hukum Islam (maqāṣid asy-sharī‘ah), seperti keadilan, pelestarian harta, dan kebaikan, memberikan dasar etis dan hukum untuk pembedaan ini. Studi ini menyimpulkan bahwa TVM hanya sesuai dengan Syariah jika diterapkan dalam kerangka transaksi ekonomi nyata, bukan dalam mekanisme keuangan yang eksploitatif. Penelitian ini masih terbatas pada analisis hukum konseptual dan tidak mengevaluasi penerapan praktisnya dalam industri keuangan Islam. Studi-studi di masa depan didorong untuk mengeksplorasi implementasi TVM dalam produk keuangan Islam kontemporer dan relevansinya dengan standar internasional dan kerangka regulasi.